Generating universal anti-CD19 CAR T cells with a defined memory phenotype by CRISPR/Cas9 editing and safety evaluation of the transcriptome - Pavlovic, Kristina; Carmona-Luque, MDolores; Corsi, Giulia I.; Maldonado-Pérez, Noelia; Molina-Estevez, Francisco J.; Peralbo-Santaella, Esther; Cortijo-Gutiérrez, Marina; Justicia-Lirio, Pedro; Tristán-Manzano, María; Ronco-Díaz, Víctor; Ballesteros-Ribelles, Antonio; Millán-López, Alejandro; et al. (Frontiers in Immunology, 2024)
Introduction Chimeric antigen receptor-expressing T cells (CAR T cells) have revolutionized cancer treatment, particularly in B cell malignancies. However, the use of autologous T cells for CAR T therapy presents several limitations, including high costs, variable efficacy, and adverse effects linked to cell phenotype. Methods To overcome these challenges, we developed a strategy to generate universal and safe anti-CD19 CAR T cells with a defined memory phenotype. Our approach utilizes CRISPR/Cas9 technology to target and eliminate the B2M and TRAC genes, reducing graft-versus-host and host-versus-graft responses. Additionally, we selected less differentiated T cells to improve the stability and persistence of the universal CAR T cells. The safety of this method was assessed using our CRISPRroots transcriptome analysis pipeline, which ensures successful gene knockout and the absence of unintended off-target effects on gene expression or transcriptome sequence. Results In vitro experiments demonstrated the successful generation of functional universal CAR T cells. These cells exhibited potent lytic activity against tumor cells and a reduced cytokine secretion profile. The CRISPRroots analysis confirmed effective gene knockout and no unintended off-target effects, validating it as a pioneering tool for on/off-target and transcriptome analysis in genome editing experiments. Discussion Our findings establish a robust pipeline for manufacturing safe, universal CAR T cells with a favorable memory phenotype. This approach has the potential to address the current limitations of autologous CAR T cell therapy, offering a more stable and persistent treatment option with reduced adverse effects. The use of CRISPRroots enhances the reliability and safety of gene editing in the development of CAR T cell therapies. Conclusion We have developed a potent and reliable method for producing universal CAR T cells with a defined memory phenotype, demonstrating both efficacy and safety in vitro. This innovative approach could significantly improve the therapeutic landscape for patients with B cell malignancies.